2021
DOI: 10.1029/2021ef002365
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Risk Assessment of Population Affected by Tropical Cyclones Through Joint Consideration of Extreme Precipitation and Strong Wind—A Case Study of Hainan Province

Abstract: Tropical cyclone disasters frequently occur in the southeastern coastal areas of China, and the concentration of population and economy has further increased the risk of tropical cyclone disasters in this region. The effects of tropical cyclones on populations involve a complex interaction between hazard intensity, environmental factors, exposure level, and fortification capacity. Therefore, quantifying the relationship among these factors is imperative for early warnings, risk assessments, and mitigation stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Precipitation‐driven risk regions should be attuned to precipitation‐induced floods, dam breaks, debris flows or landslides (Cao, 2015; Lei et al., 2015). Finally, fully considering the impact of complex driving forces such as strong winds, extreme rainfall, and storm surges, as well as their combined effects (Meng et al., 2021), is crucial for effective management and adaptation to tropical cyclones in Hainan and other wind‐precipitation‐driven regions.…”
Section: Discussionmentioning
confidence: 99%
“…Precipitation‐driven risk regions should be attuned to precipitation‐induced floods, dam breaks, debris flows or landslides (Cao, 2015; Lei et al., 2015). Finally, fully considering the impact of complex driving forces such as strong winds, extreme rainfall, and storm surges, as well as their combined effects (Meng et al., 2021), is crucial for effective management and adaptation to tropical cyclones in Hainan and other wind‐precipitation‐driven regions.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the comprehensive assessment approaches that combine various environmental factors (Meng et al 2021), our method only takes the MWS as a convenient hazard factor for rapid damage prediction. The damage data were integrated statistics that included all losses caused by extreme wind, heavy rainfall, and even storm surges during a TC.…”
Section: Vulnerability and Disaster Loss Curvesmentioning
confidence: 99%
“…For example, Lu et al (2018) developed an intensity index combined with wind speed and population vulnerability to evaluate the TC wind disaster risk in Zhejiang Province. Meng et al (2021) developed a comprehensive assessment approach that used maximum wind speed (MWS), extreme precipitation, and environmental factors to evaluate the rate of affected population in different return periods in Hainan Province. These methods merely classify the relative risk or risk severity categories, however, and they cannot reflect the potential damage to all the elements at risk.…”
Section: Introductionmentioning
confidence: 99%
“…However, the data are mainly the maximum or accumulated value of annual statistics [33] or TC events [6,34] from a single meteorological station. Recent studies have used meteorological data from multiple stations to depict the regional difference of hazard intensity [35,36]. These studies have indicated that Copula theory can be an effective tool for TC hazard assessment.…”
Section: Tc Hazard Assessmentmentioning
confidence: 99%